Age, but not short-term intensive swimming, affects chondrocyte turnover in zebrafish vertebral cartilage - Quan-Liang Jian; Wei-Chun HuangFu; Yen-Hua Lee; I-Hsuan Liu (PeerJ, 2018)
Both age and intensive exercise are generally considered critical risk factors for osteoarthritis. In this work, we intend to establish zebrafish models to assess the role of these two factors on cartilage homeostasis. We designed a swimming device for zebrafish intensive exercise. The body measurements, bone mineral density (BMD) and the histology of spinal cartilages of 4- and 12-month-old zebrafish, as well the 12-month-old zebrafish before and after a 2-week exercise were compared. Our results indicate that both age and exercise affect the body length and body weight, and the micro-computed tomography reveals that both age and exercise affect the spinal BMD. However, quantitative analysis of immunohistochemistry and histochemistry indicate that short-term intensive exercise does not affect the extracellular matrix (ECM) of spinal cartilage. On the other hand, the cartilage ECM significantly grew from 4 to 12 months of age with an increase in total chondrocytes. dUTP nick end labeling staining shows that the percentages of apoptotic cells significantly increase as the zebrafish grows, whereas the BrdU labeling shows that proliferative cells dramatically decrease from 4 to 12 months of age. A 30-day chase of BrdU labeling shows some retention of labeling in cells in 4-month-old spinal cartilage but not in cartilage from 12-month-old zebrafish. Taken together, our results suggest that zebrafish chondrocytes are actively turned over, and indicate that aging is a critical factor that alters cartilage homeostasis. Zebrafish vertebral cartilage may serve as a good model to study the maturation and homeostasis of articular cartilage.